Dynamics of Amphibian Community in Kerandangan Nature Reserve - Mohammad Liwa Ilhamdi; Muhammad Syazali (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Kerandangan Nature Reserve is an area with important ecological aspects in the fields of economy, culture and education. One of its ecological components is amphibians. Previous research was conducted with brief observations so that the data were not sufficient to provide an overview of community fluctuations due to dependent and independent density factors. The study aim is to analyze the dynamics of the amphibian community during the period 2013 - 2019. The field survey was conducted in 3 different years, namely 2013, 2016, and 2019. Analysis of community dynamics was carried out by comparing the composition and species diversity indexes. Whether or not there are differences in the amphibian community is determined by One Way ANOVA. We found that during the period 2013-2019 there was a change in species composition. However, when compared with the results of research in 2011, the species composition is same as the data for 2019. Species richness is relatively stable unless there is a change in data for 2013 and 2016 with the discovery of Ingerophrynus biporcatus and Kaloula baleata so that the species richness increases to 4. The results of the One Way ANOVA test showed that there was no significant difference in diversity (p > 0.05) during the 2013-2019 timeframe.